Investigation of innovation perception in athletes in terms of personality types and some demographic characteristics - Serkan Necati Metin; Tuncay Öcal (ROL Spor Bilimleri Dergisi)
This study aims to examine athletes' perceptions of innovation in terms of personality types and some demographic characteristics. Relational and descriptive analysis models were used for the purpose of the study. "Personal Information Form", "Five-Factor Personality Scale" and "Innovation in Sports Scale" were utilized as "data collection tools". The research group comprises 196 people, 89 women and 107 men, determined by random sampling. G-power 3.1.9.7 was utilized to determine the sample size. As a result of the study, it was determined that although there are significant differences in the innovation perceptions of athletes when evaluated with different demographic characteristics, it has a small effect. Apart from this, it was determined that the explanatory rate of athletes' personalities on their perceptions of innovation was low, but there was a significant positive relationship. As a result, it is understood that athletes' demographic and personality characteristics are limited in understanding their perceptions of innovation.